SOSIALISASI POTENSI DESA PESAWAHAN SEBAGAI JASA LINGKUNGAN GUNA MENDUKUNG PEMBANGUNAN BERKELANJUTAN - Sillak Hasiany; Fajriharish Nur Awan; Bambang Prasetio; Intan Andriani Putri; Nabilla Putryandri Alifa (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Sustainable development is an approach to planning, implementing and managing the development process by taking into account the needs of the present without compromising the ability of future generations to meet their own needs. Dissemination of the potential of Pesawahan Village as environmental services that contribute to supporting sustainable development is carried out with the aim of increasing public understanding of the importance of protecting and managing Pesawahan Village as a valuable environmental resource. Socialization efforts are carried out by holding meetings and counseling for the local community. The results of this socialization show that there is an increase in public awareness about the importance of preserving and managing Pesawahan Village in a sustainable manner